2003
DOI: 10.1021/ic0346376
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Dependent Dynamics of the MQ→ReII Excited-State Electron Transfer in [Re(MQ+)(CO)3(dmb)]2+

Abstract: The Re-->MQ(+) MLCT excited state of [Re(MQ(+))(CO)(3)(dmb)](2+) (MQ(+) = N-methyl-4,4'-bipyridinium, dmb = 4,4'-dimethyl-2,2'-bipyridine), which is populated upon 400-nm irradiation, was characterized by picosecond time-resolved IR and resonance Raman spectroscopy, which indicate large structural differences relative to the ground state. The Re-->MQ(+) MLCT excited state can be formulated as [Re(II)(MQ*)(CO)(3)(dmb)](2+). It decays to the ground state by a MQ*-->Re(II) back-electron transfer, whose time const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
1
17
0
1
Order By: Relevance
“…These observations are consistent with appearance of an additional intermediate, 3. 26 (dmb is 4,4 0 -dimethyl-2,2 0 -bipyridine) in CH 2 Cl 2 , λ max = 630 and 380 nm. The 400 nm absorption includes significant contributions from H 2 Q •+24 and HQ • , 5,27 the latter of which is formed by a following reaction, as discussed below.…”
Section: Section: Kinetics Spectroscopysupporting
confidence: 86%
“…These observations are consistent with appearance of an additional intermediate, 3. 26 (dmb is 4,4 0 -dimethyl-2,2 0 -bipyridine) in CH 2 Cl 2 , λ max = 630 and 380 nm. The 400 nm absorption includes significant contributions from H 2 Q •+24 and HQ • , 5,27 the latter of which is formed by a following reaction, as discussed below.…”
Section: Section: Kinetics Spectroscopysupporting
confidence: 86%
“…Complex 2Re(BiPy‐Me) 2 containing viologen‐type N‐methyl‐4,4’‐bipyridinium ligand (MQ + ) demonstrates rich electrochemistry both in oxidation and reduction modes (Figure 8) due to availability of low lying filled and empty orbitals of the aromatic ligands and a variety of charge transfer processes, which may occur in these systems [65–74] …”
Section: Resultsmentioning
confidence: 99%
“…Complex 2Re(BiPy-Me) 2 containing viologen-type N-methyl-4,4'-bipyridinium ligand (MQ + ) demonstrates rich electrochemistry both in oxidation and reduction modes (Figure 8) due to availability of low lying filled and empty orbitals of the aromatic ligands and a variety of charge transfer processes, which may occur in these systems. [65][66][67][68][69][70][71][72][73][74] Application of several spectro-electrochemical techniques in the study of the [Re(N N)(CO) 3 MQ] 2 + complexes [67][68][69][70]75,76] showed that CV of this type of compounds commonly display four reversible one-electron reduction waves related to successive one and two electron reduction of the diimine and MQ…”
Section: Electrochemistrymentioning
confidence: 99%
“…These systems have been extensively studied over the past few decades. Complexity in function and photophysics can be built into these systems by the use of differing ligands, such as in chromophore-quencher complexes [105][106][107] or heteroleptic complexes. [108][109][110][111][112][113][114][115][116] In addition even the apparently simplest MLCT systems may be affected by ancillary ligands that can play a significant role in the photophysics and spectroscopic properties.…”
Section: Conventional Mlct Systemsmentioning
confidence: 99%